2014
DOI: 10.1111/jgh.12540
|View full text |Cite
|
Sign up to set email alerts
|

PNPLA3 in end‐stage liver disease: Alcohol consumption, hepatocellular carcinoma development, and transplantation‐free survival

Abstract: In end-stage liver disease patients, we identified ALD to be predominantly affected by the PNPLA3 I148M variant resulting in an increased risk of HCC and reduced transplantation free survival. Genetic testing of the I148M genotype in ALD patients awaiting liver transplantation might be beneficial for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 28 publications
3
42
0
1
Order By: Relevance
“…Interestingly, in spite of their association with the development of ASH/ NASH related HCC, the correlation of the SNP with clinical characteristics and the prognostic significance was not established in this report. In contrast, previous studies demonstrated that survival free of liver transplantation was significantly lower in patients with ASH when carrying one or two G allele compared with wild-type (Friedrich et al, 2014).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Interestingly, in spite of their association with the development of ASH/ NASH related HCC, the correlation of the SNP with clinical characteristics and the prognostic significance was not established in this report. In contrast, previous studies demonstrated that survival free of liver transplantation was significantly lower in patients with ASH when carrying one or two G allele compared with wild-type (Friedrich et al, 2014).…”
Section: Discussionmentioning
confidence: 60%
“…Interestingly, although PNPLA3 polymorphism has been related to hepatic steatosis in patients with HCV infection, its association with HCC development is less clear with conflicting results. Some studies have demonstrated that the GG genotype effect the risk of HCC development (Falleti et al, 2011;Sato et al, 2014), while most other studies have reported no such association (Nischalke et al, 2011;Guyot et al, 2013;Friedrich et al, 2014). For patients with HBV infection, recent data reported that PNPLA3 polymorphism was independently associated with hepatic steatosis, but not with advanced fibrosis and HCC development (Vigano et al, 2013;Brouwer et al, 2015;Zampino et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Severe alcoholic hepatitis has considerable associated mortality [8,9,[11][12][13] but apart from one small series, published in abstract form [33], which identified rs738409:G as a risk factor for developing severe alcoholic hepatitis, the potential impact of this genetic polymorphism on disease presentation, progression and outcome has not been evaluated. The results of the present study have helped clarify these associations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore there is growing evidence that rs738409:G influences several other important aspects of alcohol-related liver disease; thus, carriage of the G allele is associated with earlier development of cirrhosis, independently of the age of onset of at-risk alcohol consumption [32]; more rapid progression towards decompensated disease [33]; a reduction in transplantation-free survival [33] and poorer outcomes following development of hepatocellular carcinoma [34].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, variants in the PNPLA3 gene had the strongest signal with GWAS-significance. Interestingly, a crosssectional study following 105 alcoholic cirrhotic patients with end-stage liver disease reported that rs738409 [G] was associated with shorter time to hepatic decompensation and reduced transplantation-free survival [31]. These potentially interesting findings linking PNPLA3 to patient prognosis are still awaiting replication.…”
Section: Alcoholic Liver Diseasementioning
confidence: 99%